A Regional Look at Cars in A Mixed Park (Eurasian Journal of Engineering and Technology, 2022)
The improvement of the motor transport sector creates a basis for reducing transport costs and increasing competitiveness. Management of motor transport through economic relations and consistent improvement of the routing system and the activities of the car and the interaction of types of transport, Innovation in it and invocations the normative-legal framework, which provides for the acceleration of its policy, is increasingly improvement is taking place. Given the passage of cargo flows through the Republic of Uzbekistan, prospective international transport corridors are being formed, opportunities of Uzbek auto-carriers to use international transport communications are growing, and multimodal cargo transportation is developing. Sustainable development of auto transport certification system improving new techniques, advanced diagnostics and repairs application of technology, renewal of the fleet of motor vehicles, consistent inspection and control of vehicle safety